Globalization and Educational Realities in Ukraine - Shapovalov, Anatoliy (Filosofiya osvity. Philosophy of Education, 2008)
The essence and main tendencies of globalization in the contemporary world economic, cultural, scientific-informational space is reviewed in the article. These tendencies define the contemporary education and educational activity requirements, in particular, the necessity to overcome the gap between science and education, the scientific achievements and the level of professional education. The integration processes in the sphere of education are analyzed. Author emphasizes, that University should become the centre of educational and scientific integration. It is argued that in a cultural sense a modern University should be transformed into the centre of spiritual and intellectual development. The state of the higher education in Ukraine and perspectives of its European integration are described in the article.